Transcriptomic analysis of mammary gland tissues in lactating and non-lactating dairy goats reveals miRNA-mediated regulation of lactation, involution, and remodeling - Peng, Yanan; Duan, Xinhua; Zhang, Linfan; Guo, Yiyi; Cao, Jinlin; Ao, Weiping; Xuan, Rong (Frontiers in Cell and Developmental Biology, 2025)
BackgroundDynamic changes in the mammary gland during lactation and the dry period involve proliferation, secretion, apoptosis, and remodeling of mammary epithelial cells. MicroRNAs (miRNAs) are recognized as critical regulators of mammary gland development and lactation. However, their expression patterns and regulatory mechanisms at different lactation stages—particularly during mammary involution and remodeling—remain poorly understood in dairy goats.MethodsIn this study, high-throughput sequencing was employed to analyze miRNA expression profiles in goat mammary tissues at five key stages: late gestation (LG), early lactation (EL), peak lactation (PL), late lactation (LL), and the dry period (DP). Differential expression analysis, miRNA clustering, Gene Ontology (GO) annotation, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were performed to predict the functions of target genes. A miRNA-mRNA regulatory network associated with mammary gland development was constructed, and functional validation experiments were conducted to confirm key regulatory relationships.ResultsA total of 1,120 miRNAs were identified, including 408 known and 712 newly predicted miRNAs. Among them, 383 were significantly differentially expressed, with the largest number observed between the dry period and late gestation. Six expression-specific miRNA clusters were identified. Functional enrichment analysis indicated that these miRNAs may regulate epithelial cell proliferation, apoptosis, and tissue remodeling by targeting pathways such as energy metabolism, cell adhesion, and the PI3K/Akt signaling pathway. IGF1R was identified as a key regulatory gene in the miRNA-mRNA network related to mammary gland development. Experimental validation showed that chi-miR-423-3p inhibited mammary epithelial cell proliferation, induced G1/S cell cycle arrest, and promoted apoptosis by targeting IGF1R and suppressing the PI3K/Akt pathway.ConclusionThis study highlights the dynamic regulatory roles of miRNAs in the goat mammary gland across lactation stages. Notably, the miR-423-3p/IGF1R axis is a key regulator of mammary remodeling during the dry period, offering new insights into the molecular basis of mammary gland functional transitions.